Triphosgene in Heterocyclic Chemistry, Novel Synthesis of Pyrazolo (2, 3-c) Quinazoline from 2-Acetamido Acetophenone Hydrazone - Al-Saad, M.A.; Jum'H, A.A.M. (Asian Journal of Chemistry, 2010)
5-Methyl-3-pbenyl pyrazolo-[2,3-c]-quinazoline-2-one was prepared from the reaction of triphosgene (BTC) with 2-acetamido acetophenone hydrazone.